“Aplicación de tres dosis de biol con fertirriego en cultivo de tomate (Solanum lycopersicum) en el cantón Quito provincia de Pichincha. - Quishpe Cushicondor, Francisco Javier (2021)
This research project was carried out in the Province of Pichincha, Canton Quito, Parroquia de Amaguaña, San Fernando Neighborhood on the property of Mr. José Quishpe. In order to apply three doses of biol through fertigation to know the development and production of the kidney tomato plant (solanum lycopersicum) variety Pietro. An investigation was established whose objective was to apply three doses of biol by fertigation in the Pietro variety kidney tomato plant, this exploration is based on data obtained on growth (90 days) and production (90 days). The treatment under study was the Pietro variety kidney tomato evaluated every week. For this, a completely randomized block design was established, it is structured by 4 treatments Dose 1 (1% of biol + 99% of water), Dose 2 (2% of biol + 98% of water), Dose 3 (3% of biol + 97% of water) and Chemical Control, 6 repetitions and an experimental unit, giving a total of 24 units, the variables that were evaluated are, physical-chemical characteristics of the biol, number of flowers, plant height, production and economic analysis. In the field, the soil analysis was carried out, obtaining a soil of loamy texture, whose percentage is 39% sand, 40% silt and 21% clay with a medium acid pH of 5.96. It was determined that dose 3 (3% biol + 97% water) was the best option because it obtained greater profitability in terms of production, plant development and number of flowers. It was determined that the tomato cultivation project through fertigation system had profitability, a benefit to continue working on it.